Utilizing Program of Vacant Land on Public Facilities for Diabetes Mellitus Self-Medication Parks in Benteng Village, Bogor Regency - Siti Sa’diah; Qodarian Pramukanto; Ninuk Purnaningsih (Tropical Biopharmaca Research Center, IPB University, 2022)
The prevalence of diabetes in Indonesia has increased substantially in the last 30 years, where individual chances of developing diabetes are higher for women than for men; and level of education is negatively related to diabetes mellitus. Independent therapy garden, is one of the functions of public park which is designed thematically for therapy (medication).The objectives of Program are: (1) Development of a participatory Diabetes Mellitus Self-therapy Garden at partner locations; (2) Cultivation training and education in using/processing of medicinal plants for self-therapy for Diabetes. Program partners are the Kecapi Posyandu RW 6 Benteng Village Bogor Regency, West Java Province. Partner problems are: (1) There are a large number of elderly people who have the potential to suffer from Type 2 Diabetes; (2) Lack of knowledge of partners and residents around partner locations about Diabetes: its characteristics, treatment and prevention; (3) Lack of skills in cultivating and processing of medicinal plants to maintain health, especially diabetes. The participatory approach was carried out by involving partners from the beginning of the program, started from discussing the activity plan, determining the location of the public facility land to be built into a therapy park, and determining program participants. The determination of the location of the park was chosen based on area that was easily visited by residents, so that they can interact with fellow residents in the park. Education about diabetes therapy was carried out by conveying information about diabetes mellitus and how to handle it. Education on the use of medicinal plants, processing them, concocting them, was carried out in practice. There has been an increase in knowledge, skills, and positive attitudes in the prevention and treatment of diabetes independently by partners. The sustainability of the program is carried out by providing diabetes self-therapy manuals, and mentoring through groups through periodic discussions.